L'enseignement de la sante et de la sécurité au travail a l'école: Une illusion institutionnelle pour penser l'évolution des pratiques de prévention - HELENE CHENEVAL-ARMAND; JACQUES GINESTIE (Metaichmio Publications, 2011)
The curriculum of initial vocational training in France of air-conditioning technicians has been modified to take into account how occupational hazards prevention is conducted in professional practices. Three distinct organisations, based on general education, vocational training and work placements in companies, must be combined in this curriculum. The evolution of practices presumes that coherence is built between these references. The perception of the concept of risk is different, while professional standardises them, school sacralise them. Initial training plays a major role in attitude evolution. Our work shows the tension which exists between the learning concerned by the professionals in their practises and those carried by educational establishment. We thus could qualify the differences between effective practises of the professionals and school practises. For as much, we also show that the pupils spontaneously adopt as reference the practises of the professionals who assert themselves. The process of teaching-learning is some thus reduced and its seriously decreased effectiveness; under these conditions, it is enabled to us to doubt the effective and real evolution of the practises of prevention corresponding to institutional aims.